Answer:
y=3x.........1
y=x^2-10.......2
substituting value of eq 1 to 2
3x=x^2-10
x^2-10-3x=0
x^2-3x-10=0
x^2-5x+2x-10=0
X(x-5)+2(x-5)=0
(x-5)(X+2)=0
then
X=5 or X=-2
again
y=??
when X=5
y=3×5=15
when X=-2
y=-6
It would be the last one. The dots must be open and x must move to the right.
Answer:
This means that f(x)→∞ as x→−∞ and f(x)→∞ as x→∞.
Step-by-step explanation:
Since the leading term of the polynomial (the term in a polynomial which contains the highest power of the variable) is x4, then the degree is 4, i.e. even, and the leading coefficient is 1, i.e. positive.
This means that f(x)→∞ as x→−∞ and f(x)→∞ as x→∞.
To get t on one side, we have to use inverse operations to get rid of the 5.
1. Use inverse operation of multiplication to get rid of 5. Which would be division.
2. Divide both sides by 5.
5t/5 = 7 1/2 / 5
3. Solve.
5t/5 = t and 7 1/2 /5 = 1 1/2
7.5 / 5 = 1.5
Therefore, your answer would be C. divide both sides by 5, and the answer is 1 1/2.